2017
DOI: 10.1596/1813-9450-8004
|View full text |Cite
|
Sign up to set email alerts
|

The Motherhood Penalty and Female Employment in Urban India

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
(29 reference statements)
4
18
1
Order By: Relevance
“…For women, a central value and normative expectation is that they “ought” to become mothers (see Russo, 1976). To cite only a few examples, in Australia, motherhood is thought to be an essential component of being a woman (e.g., Holton et al, 2009); in both Mexico and the United States, it is seen as a gender role that “completes” women (Chrisler et al, 2013); and for women in India, it is seen as normative (Das & Zumbyte, 2017) and “ordinary and natural” (Riessman, 2000). Consequentially, in the United States, women who do not have children are seen as cold (Cuddy et al, 2004), are judged to be less satisfied with their life, and to even elicit moral outrage from others (Ashburn-Nardo, 2017).…”
Section: Palliative Function Of System Justificationmentioning
confidence: 99%
“…For women, a central value and normative expectation is that they “ought” to become mothers (see Russo, 1976). To cite only a few examples, in Australia, motherhood is thought to be an essential component of being a woman (e.g., Holton et al, 2009); in both Mexico and the United States, it is seen as a gender role that “completes” women (Chrisler et al, 2013); and for women in India, it is seen as normative (Das & Zumbyte, 2017) and “ordinary and natural” (Riessman, 2000). Consequentially, in the United States, women who do not have children are seen as cold (Cuddy et al, 2004), are judged to be less satisfied with their life, and to even elicit moral outrage from others (Ashburn-Nardo, 2017).…”
Section: Palliative Function Of System Justificationmentioning
confidence: 99%
“…Childcare was a significant constraint, more so in urban areas where families tended to be nuclear. Das and Zumbyte (2017) for instance find that having a young child in the home depresses mothers' employment, a relationship that has intensified over time. The quality and affordability of childcare also came up frequently in the qualitative discussions, with many women saying that the facilities available (even paid ones) were not of good quality and the responsibility of tutoring and supervising children came down entirely to mothers.…”
Section: Women Need Jobs That Are Safe Pay Adequately and Offer Flementioning
confidence: 99%
“…While gender differences in labor market indicators are tapering off in many parts of the world (Goldin, 2014), the presence of women and even more so of mothers in labor markets remains low in many developing countries. 1 One much discussed case is India (Klasen & Pieters, 2015;Das & Zumbyte, 2017;Verick, 2018), where less than 30% of women participate in the labor force notwithstanding improvements in socio-economic and demographic conditions in recent years. The country's overall female labor force participation rate has even dropped from 22 percent in 1987 to 17 percent in 2011 (Klasen & Pieters, 2015), with the labor force participation of women typically falling around first motherhood (see Bedi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In South Asia, the female labor force participation rate ranges from less than 30% in Pakistan to 80% in Nepal. SeeVerick (2018) for more details.2 According to data from the Indian National Sample Survey (NSS), the gap between the labor force participation of mothers and married non-mothers in urban area was 7.5 percentage points in 2011(Das & Zumbyte, 2017).3 Based on NSS 2011 data, in the Indian context, a majority (70%) of married women (aged 25-55) reported that they stay out of the labor market due to domestic obligations.…”
mentioning
confidence: 99%